Condicionantes institucionais à execuç\~ao de projetos de infraestrutura: Financiamento de longo prazo - Miguel Vazquez; Michelle Hallack; Renato Queiroz (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– Capital stock in residential structures, as well as the distribution of its appropriation and ownership among families are fundamental determinants of the wealth, welfare and productivity of the economy. As part of a broad project on the stock of capital of the Brazilian economy in the 20th Century, this paper presents estimates of the value of the stock in residential structures in Brazil from 1970 to 1999. The macroeconomic focus neglects the distributive and allocative effects of residential property and use. The model of hedonic prices is applied to data on the values of rents and other characteristic of the residences - number of rooms and bathroom, construction material, accesss to public servies such as electricity, water, garbage collection, among other - to estimate the hedonic prices of these attributes. After the introduction, the models discusss the specification of the hedonic model as well as of other hypothesis used in the estimation. The third section describes the database. The fourth section discusses estimation methods and problems. The fifth section analyses the results showing, on the one hand, that they seem to be quite reasonable in international perspective, and on the other that attributes related to the public infrastructure have fundamental impactos on the value to residential stock. The paper concludes calling attention to the high social return of public investments in infrastructure, and in particular of the investments and financing of housing projects for low income families which can have substantial effectos on the wealth, productive capacity, and welfare of Brazilian society.
Keywords: G32; G38; L22; G31; 330; residential structure; housing wealth; hedonic prices; Brazil